Electronic Skin: Bioinspired Interlocked and Hierarchical Design of ZnO Nanowire Arrays for Static and Dynamic Pressure‐Sensitive Electronic Skins (Adv. Funct. Mater. 19/2015). (May 2015) - Ha, Minjeong; Lim, Seongdong; Park, Jonghwa; Um, Doo‐Seung; Lee, Youngoh; Ko, Hyunhyub
Abstract : Flexible electronic skins (e‐skins) with static and dynamic tactile sensing capabilities are demonstrated on page 2841 by H. Ko and co‐workers based on the interlocked geometry of hierarchical polydimethylsiloxane (PDMS) micopillar arrays decorated with ZnO nanowire forests. While the e‐skin in a piezoresistive mode enables a static pressure detection with high sensitivity, the piezoelectric e‐skin mode permits the dynamic sensing of high frequency vibrations.